Análise crítica do sistema de abastecimento de água da cidade de Cuiabá – MT - Dambros, Ildisneya Velasco (2013)
In this context, this dissertation aims to critical analysis of the water supply system of the city of Cuiabá in order to identify the main factors that have caused the flashing light of the methodology developed by Totsuka (2004) , which identifies the main cause the shortage of water or flashing system . Operational, commercial and information of the water supply system, obtained from the Sanitation Company of the Capital were analyzed - SANECAP for the period 2007-2011 , and using simple tools such as arithmetic averages was possible to visualize the temporal and spatial evolution of the population , coverage of water supply sources and the variables that compose the system as a whole and each subsistema during the study period , as volume produced , volume consumed, percapta respective values and losses , the latter being considered indicators by the system but with questionable results because of the uncertainties presented in the data collection process. As a result can also be seen that although Cuiabá present surplus water availability for the entire population and provide a total flow produced per capita value exceeding the national average supply , the water supply is still done intermittently , as a consequence of poor management system by discontinuing the necessary actions and lack of financial resources. In light of the proposed methodology , the causes of intermittency in the city under study can be framed simultaneously on the Scarcity and Economic Mismanagement Category, common reality in countries with limitations in financial resources associated with strong political interference.